Digit Ratio in the Groups of Women and Men Practising and Non-practising Sports and Its Relations to the Somatic Features and Motoric Fitness - Magdalena Mońka; Jadwiga Pietraszewska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
The aim of the paper was to evaluate the digit ratio between groups of sporting and non-sporting women and men, and attempt to determine a value typical for athletes of each gender. Additional-ly, the aim was to evaluate relations of the digit ratio with both the somatic structure and motor fitness, which could then be used to improve on sports selection criteria. The research material comprised 22 anthropometric measurements together with results of four motor fitness tests of students active in various sports disciplines. The control group comprised students who had never practiced sport. The sporting students showed significantly lower digit ratios compared to the control group of non-sporting students. Correlations between the digit ratio and features of the body structure were low. Both sexes recorded significant nega-tive correlations between the digit ratio and handgrip strength, as well as with the long jump length. Those with a lower value of the digit ratio had better predispositions to practicing sports.